Study on the Effect of Sociocultural Aspects on Consumer Interest Purchasing Japandi (Japanese-Scandinavian) Household Goods in Indonesian Marke - Scholus, Jessica Elisabeth; Pranata, Jefri; Andriani, Nawangwulan Rizqi (Yayasan Ilomata, 2023)
The Indonesian civilization exhibits a profound historical association with and a high level of familiarity with wood as a material, which shaped Indonesia's sociocultural values. However, with the advancement of civilization and the pervasive impact of Western culture, wood has undergone a transformation, becoming a commodity that is predominantly esteemed for its practical usefulness. The significance of wood as a symbol of diplomatic or social rank has diminished throughout time, particularly in the context of palatial environments. Hence, the primary objective of this research is to investigate the influence of sociocultural factors on the inclination of the Indonesian market to adopt the Japandi (Japanese-Scandinavian) style in household goods such as furniture and home accessory design, which is distinguished by its emphasis on minimalistic aesthetics and practicality. In order to reveal these insights, the researchers used the buying intentions theory combined with quantitative explanatory analysis to clarify the observed phenomena and derive conclusions. Data will be gathered via questionnaires employing random sampling, with a focus on the Indonesian market as the target population. The results of the study indicate that social and cultural elements play a significant role in shaping the intention to buy Japandi (Japanese-Scandinavian) home furnishings in Indonesia.